Development of a novel hybrid hydrogen generator incorporated into a combined system for buildings in sustainable communities - Gursoy, Mehmet; Dincer, Ibrahim (ELSEVIER SCIENCE SA, 2024)
The development of a new hybrid hydrogen generator, using both photoelectrochemical process and conventional electrolysis, integrated into a combination system for buildings is a major step forward in the quest for sustainable energy solutions in cities where it is specifically designed, implemented and evaluated for incorporation into sustainable community systems. A significant advantage of this hydrogen generator is the ability to produce hydrogen constantly, regardless of the absence of solar irradiation. Furthermore, both electrolyzers contribute to a rise in the amount of hydrogen produced. Furthermore, the utilization of PEC electrolysis for hydrogen generation results in a significant reduction in the overall power requirements of the system. This new study investigates an integrated power system that produces electricity from solar energy and tackles issues related to freshwater supply, hydrogen production, and heating/cooling demands. The purpose of this research is to integrate advanced system components, including a solar power tower system, a combined Brayton-Rankine cycle, a multi-effect desalination (MED) unit, a new hybridized hydrogen generator system, an absorption cooling cycle (ACS), and a hydrogen storage and refuelling station. The overall energy efficiency is determined to be 49%, while the exergy efficiency becomes 46.2%.
Keywords: Buildings; Community; Solar energy; Hydrogen production; Electrolysis; Energy; Exergy; Efficiency; SOLAR; PERFORMANCE; REACTOR; DESIGN; Construction & Building Technology; Energy & Fuels; Engineering